2021
DOI: 10.1021/acs.jafc.1c05978
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Synthase Gene OtLIS Confers Wheat Resistance to Sitobion avenae by Regulating Linalool Emission

Abstract: Sitobion avenae (Fabricius) is a major insect pest of wheat worldwide that reduces crop yield and quality annually. Few germplasm resources with resistant genes to aphids have been identified and characterized. Here, octoploid Trititrigia, a species used in wheat distant hybridization breeding, was found to be repellent to S. avenae after 2 year field investigations and associated with physiological and behavioral assays. Linalool monoterpene was identified to accumulate dominantly in plants in response to S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…63,64 Zhan et al showed that OtLIS encoding terpene synthase conferred resistance to S. avenae by modulating linalool emission before and after aphid feeding. 65 In a previous study using olfactometer assays, S. avenae was attracted to pentadecane, butylated hydroxytoluene, tetradecane and ⊎-caryophyllene, but was repelled by naphthalene. 66 In our study, the relative content of rice VOCs changed in response to exogenous ABA; the total number of VOCs released in response to ABA was declined slightly, and compounds that functioned in attracting or resisting aphids also changed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…63,64 Zhan et al showed that OtLIS encoding terpene synthase conferred resistance to S. avenae by modulating linalool emission before and after aphid feeding. 65 In a previous study using olfactometer assays, S. avenae was attracted to pentadecane, butylated hydroxytoluene, tetradecane and ⊎-caryophyllene, but was repelled by naphthalene. 66 In our study, the relative content of rice VOCs changed in response to exogenous ABA; the total number of VOCs released in response to ABA was declined slightly, and compounds that functioned in attracting or resisting aphids also changed.…”
Section: Discussionmentioning
confidence: 96%
“…Zhan et al . showed that OtLIS encoding terpene synthase conferred resistance to S. avenae by modulating linalool emission before and after aphid feeding 65 . In a previous study using olfactometer assays, S. avenae was attracted to pentadecane, butylated hydroxytoluene, tetradecane and β‐caryophyllene, but was repelled by naphthalene 66 .…”
Section: Discussionmentioning
confidence: 96%
“…The metabolic engineering of A. thaliana with berberine via the integration of the BBE gene from B. lyceum has been reported to be successful in herbivorous pest management [ 220 ]. In addition to this, genetically modified crops are also useful for attracting parasitoids or enemies of pathogens [ 221 , 222 ]. However, inadequate understanding of the biosynthetic pathways of plant-specialized metabolism, inadvertent effects of rerouting plant metabolism, suboptimal transgene design and demonstration procedures, and the stipulation for tissue-specific output of combative substances to ramp up herbivore resistance are all factors that limit current plant genetic engineering strategies [ 211 ].…”
Section: Metabolic Engineering In Biotic Stress Resistance Breedingmentioning
confidence: 99%
“…Wheat is one of the main grain products responsible for supporting the world's human population [17]. Sitobion miscanthi (Takahashi) is a major insect pest of wheat, which reduces crop yield and quality annually [18]. Because of the urgent need for sustainable agriculture and for reducing reliance on pesticide, increasing attention has been paid to conservation practices that seek to increase the biological control efficacy in agroecosystems [19,20].…”
Section: Introductionmentioning
confidence: 99%